Analysis of the state of plant cover of the Berezovka river basin of the West-Kazakhstan region based on NDVI (Journal of Geography and Environmental Management, 2021)
In the conditions of intensive development of natural complexes, the basins of small rivers undergo irrevocable changes, since they are particularly vulnerable geosystems due to their small morphometric characteristics. At the same time, being small geosystems, they are the most important links in the circulation flows of substances and energy. One of these small rivers is the Berezovka River in the Burlinsky District of the West Kazakhstan Oblast.This article presents the results of studies vegetation cover dynamics of steppe landscapes in the Berezovka River basin for the period from 1985 to 2019, which has undergone significant changes for decades as a result of anthropogenic and technological impacts. The development of the Karachaganak Oil and Gas Condensate Field had a significant impact on the agricultural landscapes of this territory.As the resultant parameter, the NDVI vegetation index was used as one of the ecological and climatic indicators, which was determined based on geoinformation processing of satellite images of the area under study. The scientific and practical significance of this study is determined by the fact that the analysis of changes in vegetation cover in different periods was carried out, which allows us to trace certain dynamics.In the course of the studies of the vegetation cover of the territory, it was revealed that significant areas were still in critical condition, despite a slight increase in NDVI indicators due to the natural increase in steppe landscapes. The research results are confirmed by the cartographic material compiled from satellite images.
Keywords: West Kazakhstan region, the Berezovka River basin, the NDVI, steppe landscapes, Karachaganak Oil and Gas Condensate Field